Effect of using Walk-In-Place Interface for Panoramic Video Play in VR - Muhammad, Azeem Syed; Hwang, Jae In; Ahn, Sang Chul (SUI'16: PROCEEDINGS OF THE 2016 SYMPOSIUM ON SPATIAL USER INTERACTION, 2016)
This paper describes the use of walk-in-place (WIP) interface to control the speed of 360-degree panoramic virtual reality (VR) video on a head-mounted display and through a pilot user study, the effect of using this interface with respect to the amount of simulator sickness and presence in the environment felt by the user is evaluated. The results are compared with traditional 360-degree VR video experience.